KALENDER PADA ZAMAN NABI MUHAMMAD Peralihan Hitungan Waktu dari Tahun Gajah ke Tahun Hijrah - Masyhudi (Program Studi Sejarah Peradaban Islam Fakultas Adab dan Humaniora UIN Sunan Ampel Surabaya, 2023)
Abstract: The Prophet Muhammad migrated on the 12th of Rab>i' al-Awwal in the 13th year of his prophethood and this gave rise to different conversion issues in the Gregorian calendar. Some converted in March 622 AD, while others converted in September 622 AD. The purpose of this article is to discuss the problem of conversion by finding the root of the problem by looking at the calendar aspects of the Elephant year and the Hijrah year which were in effect during the time of the Prophet Muhammad. This research uses historical methods with a philological approach. The results of this research show that there are three calendar systems in the world, namely the solar system (sun), the lunar system (rising moon), and the luni-solar system (a combination of solar and lunar years). Then, the Hijrah of the Prophet Muhammad was on 12 Rabi>' al-Awwal in the 13th year of the prophethood or 53 years of the Elephant, the correct conversion is March 622 AD. Keywords: Calendar of the time of the Prophet Muhammad, Elephant year, Hijrah year